Pertumbuhan Populasi Kopepoda Harpacticoid, Tigriopus sp. dengan Jenis Pakan Mikroalga yang Berbeda - Sutomo Sutomo (Jurnal Perikanan Universitas Gadjah Mada, 2007)
The objective of this research was to know the effect of different microalgae diets on the population growth of copepod, Tigriopus sp. The experiment was conducted in 60 ml plastic petridish. One individual of eggs-carrying female copepod were reared in each petri, fed different microalgae diets (Tetraselmis sp., Isochrysis galbana strain T.iso, Chaetoceros gracilis, Nannochloropsis oculata, Thalassiosira sp. and I. galbana) as treatments in 4 replicates. Observations were carried out to count the number of individual copepod, under binocular microscope. The result of one way analysis of variance showed that there were significantly different among the treatments on the population growth of the copepod (P